Primeiro registro de Anthonomus tomentosus (Faust) (Coleoptera: Curculionidae) na Amazônia Oriental - Adaime, Ricardo; Almeida, Rildo Pessoa; Pereira, José Francisco; Marsaro Júnior, Alberto Luiz; Rosado-Neto, Germano Henrique (EntomoBrasilis, 2019)
Resumo. Anthonomus tomentosus (Faust) (Coleoptera: Curculionidae) é registrado pela primeira vez na Amazônia Oriental, a partir de frutos de Malpighia emarginata DC. coletados no estado do Amapá, Brasil. Neste trabalho também são apresentados sinas de danos aos frutos e a distribuição geográfica de A. tomentosus no Brasil. First record of Anthonomus tomentosus (Faust) (Coleoptera: Curculionidae) in the Eastern Amazon Abstract. Anthonomus tomentosus (Faust) (Coleoptera: Curculionidae) is recorded for the first time in the Eastern Amazon, from fruits of Malpighia emarginata DC. collected in the state of Amapá, Brazil. In this work we also present the signals damages on the fruits and the geographical distribution of A. tomentosus in Brazil.